Profiles of anemia among school-aged children categorized by body mass index and waist circumference in Shandong, China - Ying-Xiu Zhang (Pediatrics and Neonatology, 2021)
Background: The prevalence of childhood obesity has been increasing worldwide. The connection between iron deficiency and obesity has received much research interest. The present study examined the profiles of anemia among school-aged children categorized by obesity-related index in Shandong, China. Methods: A total of 20,172 children aged 7, 9, 12, and 14 years participated in the study, whose hemoglobin (Hb) concentration was measured by laboratory technicians. The prevalence rates of anemia among children within each subgroup categorized by body mass index (BMI), waist circumference (WC) and waist-to-height ratio (WHtR) were determined. Results: On the whole, 3.99% of boys and 6.68% of girls suffer from anemia. Disparities in the prevalence of anemia were observed between different subgroups categorized by BMI, WC and WHtR. For both boys and girls, the prevalence of anemia increased with the severity of thinness and obesity, suggesting that both severe thinness and severe obesity are associated with an elevated prevalence of anemia. Conclusion: In the era of the obesity pandemic, obesity could potentially add to the burden of anemia, suggesting that obese children should not be ignored when establishing strategies targeted at preventing anemia.